2011
DOI: 10.1088/0957-4484/22/47/475304
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of layered nanostructures by successive electron beam induced deposition with two precursors: protective capping of metallic iron structures

Abstract: We report on the stepwise generation of layered nanostructures via electron beam induced deposition (EBID) using organometallic precursor molecules in ultra-high vacuum (UHV). In a first step a metallic iron line structure was produced using iron pentacarbonyl; in a second step this nanostructure was then locally capped with a 2-3 nm thin titanium oxide-containing film fabricated from titanium tetraisopropoxide. The chemical composition of the deposited layers was analyzed by spatially resolved Auger electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Based on simulations using GIS Simulator (version 1.5) [30], the local pressure increase on the sample surface was calculated to be a factor of 30. For a fixed background pressure of 3.0 × 10 −7 mbar, this corresponds to a local pressure at the surface of about 9 × 10 −6 mbar [31]. …”
Section: Methodsmentioning
confidence: 99%
“…Based on simulations using GIS Simulator (version 1.5) [30], the local pressure increase on the sample surface was calculated to be a factor of 30. For a fixed background pressure of 3.0 × 10 −7 mbar, this corresponds to a local pressure at the surface of about 9 × 10 −6 mbar [31]. …”
Section: Methodsmentioning
confidence: 99%
“…This is especially important for the targeted functionality of the latter since it was reported that even oxidized Fe‐EBID structures maintain high conductivity [ 26 ] and their ferromagnetic properties. [ 25,30 ] This again demonstrates the potential for application in nanoelectronics.…”
Section: Figurementioning
confidence: 75%
“…To overcome the oxidation upon exposure to ambient one might use a protective capping layer as reported previously. [30] By stacking the nanostructured CNMs, one might target the fabrication of layered complex electronic Figure 2. Schematic drawing of the transfer process and the corresponding SEM images of a) EBID nanostructure on SAM on Au(111)/mica fabricated with the precursor Fe(CO) 5 (beam parameters: 15 kV, 400 pA, electron dose: 1.86 C cm −2 , AG time: 1 h); b) EBID nanostructure on SAM on Au(111)/mica fabricated with the precursor Fe(CO) 5 (beam parameters: 15 kV, 400 pA, electron dose: 2.07 C cm −2 , AG time: 1 h 27 min); c) the nanostructure depicted in (a) after transfer onto TEM grid; the red circles indicate positions of particles/defects before the transfer, which obviously lead to ruptures in the freestanding CNM; d) the nanostructure depicted in (b) after transfer process onto SiO 2 ; e) blow-up of the corresponding nanostructure; f) integrated intensity line profile with correspondingly estimated full width at half maximum values extracted from the high-magnification SEM image shown in (e).…”
Section: Functional Hybrids Comprising Metallic Nanostructures Connecmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strategy to increase the metal content and/or change the microstructure consists in the application of post-growth purification steps [37][38][39]. In order to avoid the surface oxidation of the magnetic nanostructures, the use of protective shells have been found to be very effective [31,40].…”
Section: Introductionmentioning
confidence: 99%